Natural products as chemo-radiation therapy sensitizers in cancers - Nisar, S.; Masoodi, T.; Prabhu, K. S.; Kuttikrishnan, S.; Zarif, L.; Khatoon, S.; Ali, S.; Uddin, S.; Akil, A.S.; Singh, M.; Macha, M.A.; Bhat, A.A. (Elsevier, 2022)
Cancer is a devastating disease and is the second leading cause of death worldwide. Surgery, chemotherapy (CT), and/or radiation therapy (RT) are the treatment of choice for most advanced tumors. Unfortunately, treatment failure due to intrinsic and acquired resistance to the current CT and RT is a significant challenge associated with poor patient prognosis. There is an urgent need to develop and identify agents that can sensitize tumor cells to chemo-radiation therapy (CRT) with minimal cytotoxicity to the healthy tissues. While many recent studies have identified the underlying molecular mechanisms and therapeutic targets for CRT failure, using small molecule inhibitors to chemo/radio sensitize tumors is associated with high toxicity and increased morbidity. Natural products have long been used as chemopreventive agents in many cancers. Combining many of these compounds with the standard chemotherapeutic agents or with RT has shown synergistic effects on cancer cell death and overall improvement in patient survival. Based on the available data, there is strong evidence that natural products have a robust therapeutic potential along with CRT and their well-known chemopreventive effects in many solid tumors. This review article reports updated literature on different natural products used as CT or RT sensitizers in many solid tumors. This is the first review discussing CT and RT sensitizers together in cancer.